Intrathoracic Displacement of the Humeral Head with Polytrauma: Case Report - Sasnauskas, Kipras; Vrublevski, Robert; Masionis, Povilas; Ryliškis, Sigitas (Lietuvos chirurgija, 2024)
Intrathoracic displacement of the humeral head is rarely documented due to high mortality of the trauma. As a result, there is no clear consensus about how such case should be approached. In this report we reviewed our successful case, and reviewed the literature. The patient arrived after car accident with a broken humerus and upon taking X-ray found to have the humeral head lodged in the chest cavity. After humeral head removal and arthroplasty, patient was discharged without complications. In literature several cases were found in which a patient usually suffers because of high energy trauma with arm typically in abducted position. In all cases treatment involves removing humeral fragment from chest and prosthetic arthroplasty of the glenohumeral joint. Although some authors suggest leaving humeral fragment in some cases while others suggest to always remove. Exact indications of such decision are unclear. Cases like this pose a high risk of neurological and circulatory complications, although no complications were observed in this case. Nevertheless, there have been too few similar cases described to establish a proper methodology.
Keywords: dislocation; humerus; arthroplasty; shoulder